PENGARUH GAYA KEPEMIMPINAN, MOTIVASI , DAN DISIPLIN TERHADAP KINERJA KARYAWAN PADA PT ROMINDO PRIMVETCOM CABANG MEDAN - Khamo Waruwu (JURNAL MANAJEMEN DAN BISNIS, 2018)
The purposeof thisstudywas to determine Influence ofLeadership Style, Motiveasiand Discipline Workon Employee Performance PT Romindo Primavetcom Branch Medan. The populationin this study were all employees of PT Romindo Primavetcom Branch Medan of 40 people. Descriptive research method that aim stootain information about a phenomenonat the time ofthe research conducted. The research instrument was a questionnaire/questionnaire with Likert scale models. Test requirements conducted to test normality, heteroscedasticity test. The data analysis technique use dismultiple regression techniq ues at significance level α=0.05. The results showed: (1) there was a significant effect of leadership styleon employee performance with t=3,557; (2) there is a significant relationship between motivation crimes against employee performance with t=3,392; (3) there isa significant influence between disciplines influence on the performance of employees working with t=3,898.